2008
DOI: 10.1037/a0014262
|View full text |Cite
|
Sign up to set email alerts
|

Latent structure of the alexithymia construct: A taxometric investigation.

Abstract: Despite a wealth of research on the validity of alexithymia and its association with a number of common medical and psychiatric disorders, the fundamental question of whether alexithymia is best conceptualized as a dimensional or categorical construct remains unresolved. In the current investigation, taxometric analysis is used to examine the nature of the latent structure of alexithymia. Several nonredundant taxometric procedures were performed with item sets from the 20-item Toronto Alexithymia Scale (R. M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 92 publications
5
106
1
5
Order By: Relevance
“…Specifically, our correlational approach indicated that the relationship between TAS and emotion-related ERPs was significant in a broader range of time windows than those detected by our ANOVAs. These findings are consistent with recent evidence suggesting that alexithymia is better operationalized as a dimensional, rather than a more classical, taxometric approach (Ferguson et al, 2008;Ferguson et al, 2009;Parker et al, 2008). However, we acknowledge that the relative merits of dimensional versus taxometric approaches still need to be tested more systematically.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Specifically, our correlational approach indicated that the relationship between TAS and emotion-related ERPs was significant in a broader range of time windows than those detected by our ANOVAs. These findings are consistent with recent evidence suggesting that alexithymia is better operationalized as a dimensional, rather than a more classical, taxometric approach (Ferguson et al, 2008;Ferguson et al, 2009;Parker et al, 2008). However, we acknowledge that the relative merits of dimensional versus taxometric approaches still need to be tested more systematically.…”
Section: Discussionsupporting
confidence: 91%
“…This left a final sample of 46 to be analyzed. Although much research on alexithymia has relied on a taxometric approach in which participants were typically chosen from low and high ends of alexithymia measures, recent research suggests that alexithymia is better characterized as a dimensional, rather than a taxometric, construct (Ferguson et al, 2009;Ferguson, Wiliams, O'Connor, Bibby, & O'Carroll, 2008;Parker, Keefer, Taylor, & Bagby, 2008). Consistent with this approach, we chose to test participants from a broad range of the TAS distribution, instead of considering only the low and high ends, and we analyzed our data using a correlational approach.…”
Section: Participantsmentioning
confidence: 99%
“…Indeed, so-called alexithymia-that is, difficulties in identifying and describing one's own feelings (Herbert, Herbert, & Pollatos, 2011;Parker, Keefer, Taylor, & Bagby, 2008;Taylor, Bagby, & Parker, 1991), is regarded as a stable personality trait expressed with varying degrees in the general population (Kokkonen et al, 2001;Salminen, Saarijarvi, Aarela, Toikka, & Kauhanen, 1999). High levels of alexithymia are prevalent in about 10 % of the general population and increase the risk for a number of psychiatric disorders (Taylor, Bagby, & Parker, 1997).…”
Section: Abstract Cognitive Control Emotion Event-related Potentimentioning
confidence: 99%
“…O debate tem incluído questões relativas ao facto de a alexitimia ser um traço estável de personalidade, um estado flutuante, uma defesa do ego, ou um artefacto cultural (Bach, de Zwaan, Ackard, Nutsinger, & Mitchell, 1994;Parker, Taylor, & Bagby, 1998;Wise, Mann, & Epstein, 1991). Apesar de não haver um consenso quanto à sua etiologia, vários factores parecem ser relevantes para esta resposta, quer como factores etiológicos, quer como factores que afectam a vivência da alexitimia, como por exemplo factores sociodemográficos (Parker, Keefer, Taylor, & Bagby, 2008;Taylor, 1984).…”
Section: Alexitimiaunclassified
“…Assim, para começar, a avaliação deve ser feita com medidas que considerem a alexitimia uma variável contínua e a sua leitura deve ser feita numa perspectiva dimensional em vez de categorial. Isto também tem impacto na avaliação da própria mudança ao longo da terapia, que se deve focar mais nas alterações significativas nos scores de alexitimia, numa perpectiva de grau, e não tanto em alterações de "alexitímico" para "não alexitímico" (Parker, Keefer, Taylor, & Bagby, 2008). Estes dados, em conjugação com os resultados referidos anteriormente dos estudos de genética (e.g., Jørgensen et al, 2007), apontam para a possibilidade de vários dos factores envolvidos na etiologia da alexitimia: a exposição a acontecimentos traumáticos, a qualidade das relações de vinculação na infância e factores hereditários.…”
Section: Alexitimiaunclassified